2016
DOI: 10.1111/cen.13128
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of undiagnosed adrenal insufficiency to euvolaemic hyponatraemia: results of a large prospective single‐centre study

Abstract: In a large, prospective and well-defined cohort of euvolaemic hyponatraemia, undiagnosed secondary adrenal insufficiency co-occurred in 3·8% of cases initially diagnosed as SIAD. Undiagnosed pituitary disease was responsible for 1·5% of cases presenting as euvolaemic hyponatraemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 40 publications
(86 reference statements)
4
32
3
Order By: Relevance
“…HEN was most commonly due to cardiac failure (n=129, 46.9%), renal disease (n=67, 24.2%), hepatic disease (n=62, 22.4%) and obstructive uropathy (n=17, 6.1%). The aetiology in the SIAD cohort of 573 has already been described in detail . The commonest causes were central nervous system pathology (n=148, 26%), pulmonary diseases (n=111, 19%) and malignancy (n=105, 18%).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…HEN was most commonly due to cardiac failure (n=129, 46.9%), renal disease (n=67, 24.2%), hepatic disease (n=62, 22.4%) and obstructive uropathy (n=17, 6.1%). The aetiology in the SIAD cohort of 573 has already been described in detail . The commonest causes were central nervous system pathology (n=148, 26%), pulmonary diseases (n=111, 19%) and malignancy (n=105, 18%).…”
Section: Resultssupporting
confidence: 74%
“…The only intervention by the study investigators was to ensure that the minimum recommended criteria for correct classification of hyponatraemia was obtained within 48 hours. If the initial clinical and biochemical parameters suggested underlying SIAD, laboratory parameters to exclude hypothyroidism and hypoadrenalism were collected, as previously described . As this was a noninterventional, observational study, treatment decisions were left to the supervising medical teams.…”
Section: Methodsmentioning
confidence: 97%
“…Finally, 4/70 patients with euvolaemic hyponatraemia (6%) had hyponatraemia secondary to adrenal suppression consequent upon exogenous glucocorticoid administration. We have previously shown that 3.8% patients presenting with all‐cause SIAD were reclassified as having hyponatraemia secondary to steroid insufficiency after careful assessment of cortisol dynamics . The figure in this paper is a little higher, most likely due to the higher prevalence of inhaled or oral steroids for the treatment of obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 63%
“…In a large, prospective and well-defined cohort of euvolaemic hyponatraemia in a tertiary centre, undiagnosed secondary adrenal insufficiency co-occurred in 3.8% of cases initially diagnosed as SIAD. 36 Acute glucocorticoid insufficiency should also be considered as the cause of hyponatraemia in any patient with acute neurotrauma and in patients who have been receiving long-term glucocorticoid therapy.…”
mentioning
confidence: 99%